Services Quality of Ship Agency and Services Interpersonal Communication In Shipping Companies - Yuliantini, Yuliantini; Sihombing, Sarinah; Yoanyta Octora, Theresye; Saribanon, Euis; Thamrin AR, Muhammad (Green Publisher Indonesia, 2022)
This study aims to analyze the relationship between ship agency service quality, interpersonal communication and user satisfaction at PT Buana Listya Tama, either partially or simultaneously. This study uses a quantitative method by conducting a survey, and the data is analyzed using correlation and regression. The results showed that the interpersonal communication variable was also positively correlated with customer satisfaction with a t-count value of 6.108 and greater than t-table of 1.998 so that Ho was rejected and Ha was accepted. Through the F test, it is known that the quality of service and interpersonal communication simultaneously correlates with satisfaction where F count is greater than F table (90.839 > 2.75) 50 so that Ho is rejected and Ha is accepted. The coefficient of determination (R Sguare) between variables is 0.749 or 74.9%. The contribution of service quality and interpersonal communication to customer satisfaction is 74.946%, while 25.1% is influenced by other factors not examined. 749 or 74.9%. The contribution of service quality and interpersonal communication to customer satisfaction is 74.946%, while 25.1% is influenced by other factors not examined. 749 or 74.9%. The contribution of service quality and interpersonal communication to customer satisfaction is 74.946%, while 25.1% is influenced by other factors not examined.